Etnofísica dos mecanismos de alavancas utilizados pelos agricultores na produção da farinha de mandioca, Senador José Porfírio, Pará - PEREIRA, Suely Lima (Universidade Federal da Fronteira Sul, 2022)
The article discusses the valorization of the knowledge of farmers and family farmers in the conception of differentiated approaches in science teaching in schools in the countryside. For this, we studied the equipment used by farmers in the production of cassava flour as the levers and identified the mechanisms of the presses. Participant observation and semi-structured and open interviews were conducted with three families in the municipality of Senador José Porfírio, Pará. From the ethnophysics approach, it was found that they construct the presses manually, adapt and improve the operation of the levers, according to the progress of their activities. This traditional knowledge is passed down from generation to generation, via orality, observations and lived experiences. Farmers explain the mechanisms in such a way that they relate the objective to be achieved and the effort to be spared by choosing the dimensions, shape and types of materials for the construction of the press, without having theoretical knowledge of physics. This knowledge can be used in science classes, from observation and interviews to parents or community, made by the students themselves, making the detection of the lever mechanism in various equipment, tools or movements of daily life, identifying the forces involved and how it could improve them.